Effects of alcohol drinking of employee on job engagement and interpersonal conflict at work: A test of self-control strength theory using diary study - Lee, Sunhee; Ji, Ok Young; Lee, Philseok (Korean Journal of Industrial and Organizational Psychology, 2018)
The purpose of the study was to investigate the effects of alcohol drinking of employee on job engagement and interpersonal conflict at work. In order for a better understanding of the effects, we distinguished drinking based on whom they drank with: work-related vs. non-work related. Based on self-control strength theory(Baumeister, Vohs, & Tice, 2007) and effort-recovery model(Meijman & Mulder, 1998), we hypothesized that self-control plays a key role in the process by which work-related drinking influences job engagement and interpersonal conflict. Multi-level analyses on daily survey data from a total of 367 employees for two weeks showed that as participants drank more alcohol with work-related person(s), the level of ego-depletion got worse, and as a result, job engagement faltered. As for interpersonal conflict, the effects of work-related alcohol consumption and ego-depletion varied according to the level of trait self-control. On the other hand, non-work related drinking was positively related to ego-depletion, which was related to only interpersonal but to job engagement. Theoretical and practical implications of the findings and future research directions were discussed.